2015
DOI: 10.1186/s40900-015-0003-x
|View full text |Cite|
|
Sign up to set email alerts
|

Patients’, clinicians’ and the research communities’ priorities for treatment research: there is an important mismatch

Abstract: Plain English summaryThere is some evidence that there is a mismatch between what patients and health professionals want to see researched and the research that is actually done. The James Lind Alliance (JLA) research Priority Setting Partnerships (PSPs) were created to address this mismatch. Between 2007 and 2014, JLA partnerships of patients, carers and health professionals agreed on important treatment research questions (priorities) in a range of health conditions, such as Type 1 diabetes, eczema and strok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
263
0
12

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 261 publications
(290 citation statements)
references
References 22 publications
6
263
0
12
Order By: Relevance
“…Consistent with what has been observed in other fields, 23-25 our comparison of research priorities identified by patients and caregivers with research published in Transplantation and the AJT shows a significant discrepancy. 26.7% of the research published in these journals was consistent with the 10 priorities identified by the patients, caregivers and researchers in our study.…”
Section: Discussionsupporting
confidence: 85%
“…Consistent with what has been observed in other fields, 23-25 our comparison of research priorities identified by patients and caregivers with research published in Transplantation and the AJT shows a significant discrepancy. 26.7% of the research published in these journals was consistent with the 10 priorities identified by the patients, caregivers and researchers in our study.…”
Section: Discussionsupporting
confidence: 85%
“…Collaboration between patients and healthcare professionals (including researchers) seems to be an appropriate means to capture patient perspective33 and helps prevent a potential mismatch between patient preferences and the scientific focus 34…”
Section: Writing the Trial Protocolmentioning
confidence: 99%
“…(6) Work that is genuinely new may also have limited clinical applicability if it fails to focus on what matters to patients. (7,8) There have been a number of initiatives aimed at improving patient involvement in setting research agendas, but progress is slow. Both of these errors end up effectively producing research of extremely limited clinical value; unfortunately the reward structure for medical research continues to incentivise this kind of work.…”
Section: Research Questionmentioning
confidence: 99%